Utilização da tecnologia da informação pelo fisco estadual cearense: o entrelaçamento de bases de dados de contribuintes do ICMS como ferramenta de auditoria fiscal - Soares Júnior, Juracy Braga (2007)
The Public Fiscal Auditing of Taxes faces the challenge of conforming to the new technological reality. The Fiscal Auditors’ work, which was previously based only on hard copy records, is now increasingly turning to electronic files. The arrival of the Electronic Invoice and Digital Fiscal Bookkeeping generates expectations regarding the saving of resources and processes, and at the same time it will require from such professionals a great deal of effort in the process of achieving technical and professional qualifications, aiming at meeting new demands in their work routine. The analysis of a large amount of data has gained great impulse with the arrival of extraction and file analysis systems. Some of these systems have specific readymade routines for the analysis of electronic data. Besides the pre-formatted routines, they provide tools which enable the Auditor to create suitable routines for each case. The electronic files which are received, imported or apprehended, in addition to those which can be generated from the entanglement of distinct bases, can be used as evidence of offences committed by the taxpayer. In addition to providing an instrument of comparison with formal records (accounting and fiscal), they consist, in many cases, in an autonomous source of information which provides material evidence of tax evasion. The Fiscal Auditing job carried out in companies with a great volume of large amounts of data, such as telephone and electricity companies, only becomes possible with the use of such tools. The migration of operations formalizing to the electronic environment is an irreversible reality today. It is in this environment that the continuous development of new studies which point to new work techniques becomes essential to Fiscal Auditing. This research paper determines the level in which electronic databases are used by the Fiscal Auditors of the State of Ceará. It also conducts a survey on the main electronic databases used by the aforementioned Auditors in suits against State Value Added Tax (ICMS) taxpayers. The study also elaborates the inventory and description of the main tools and cross-referencing of data, in addition to measuring efficiency, speed and increase in revenue indicators with the use of such I.T. tools.